Evolution of humoral immune response to SARS-CoV-2 mRNA vaccine in liver transplant recipients – a longitudinal study (Swiss Medical Weekly, 2023)
BACKGROUND AND AIM: Liver transplant recipients show suboptimal vaccine-elicited immune responses to severe acute respiratory coronavirus 2 (SARS-CoV-2) vaccination. This study aimed to assess real-world data on SARS-CoV-2 antibodies after the second and third SARS-CoV-2 vaccination in liver transplant recipients in Switzerland.METHODS: We enrolled liver transplant recipients who attended regular follow-up visits between 01/07/2021 and 30/04/2022 at the outpatient clinic of the Department of Visceral Surgery and Medicine at Bern University Hospital, Switzerland. Following the Swiss Federal Office of Public Health recommendations, we measured SARS-CoV-2 anti-spike IgG antibodies in 117 liver transplant recipients ≥4 weeks after the second SARS-CoV-2 mRNA vaccination from 07/2021–04/2022. In case of antibody levels of 100 AU/ml were defined as “responders”, those with 12–100 AU/ml as “partial responders” and those with